The Role of Asymmetric and Symmetric Dimethylarginine in Acute Deep Vein Thrombosis - Senol, Sefa; TEKÜMİT, HAYRETTİN; TEKÜMİT, HAYRETTİN; AKAR, İLKER; Ince, Ilker (My University, 2015)
Background: In this study, we aimed to determine the importance of asymmetric dimethylarginine (ADMA), symmetric dinnethyl arginine (SDMA), and L-arginine levels which are influenced by the endothelial dysfunction in acute deep vein thrombosis (DVT), and compare their pretreatment and post-treatment levels.